PREVENTION OF ERADICATION OF MONEY LAUNDERING CRIMES AGAINST PEOPLE WHO RECEIVE GIFTS FROM THE PROCEEDS OF CRIME: JURIDICAL REVIEW - Nur Chasanah; Mohammad Rizky Pebrianto (SYNTIFIC, 2023)
Background. Crime of Money Laundering is an act that hides or disguises the origin of money or assets obtained from the proceeds of criminal acts and then converted into assets that appear to originate from legitimate activities. Criminal acts that trigger money laundering include corruption, bribery, smuggling of goods/labor, employment/immigrants, banking, narcotics, psychotropic substances, slave trade/women/children/illegal weapons, kidnapping, terrorism, theft, embezzlement, and fraud. This research purpose was to determine legal consequences and criteria of money laundering. Research Method. This research was normative research that uses a normative juridical approach, this approach is carried out by examining all laws and regulations that are related to the problem being studied. Findings. The person who gives gift in the proceeds of the crime of money laundering is ensnared by a criminal because controlling/hiding the proceeds of a crime from which that person does not know the truth. There are no specific criteria for viewing money from the crime of money laundering, but the authorities can identify the characteristics of people who receive the proceeds of money laundering crimes, such as someone's finances that have increased too fast in a short time or it can be seen that the financial graphs in privately owned banks are increasing rapidly, strange. Conclusion. All of the criteria are not guarantee that someone has received money from the crime of money laundering. The police must go through several stages, starting from examination, investigation, and so on to ensnare someone who commits the crime of money laundering.